The Effect of Vitamin D Supplementation on the Androgenic Profile in Patients with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of Clinical Trials - Azadi-Yazdi, Maryam; Nadjarzadeh, Azadeh; Khosravi-Boroujeni, Hossein; Salehi-Abargouei, Amin (Hormone and Metabolic Research, 2017)
It is suggested that vitamin D status is associated with androgenic profile in women with polycystic ovarian syndrome (PCOS). Although several clinical trials are known in this regard, the results were inconsistent. Therefore, this study was aimed to conduct a systematic review and meta-analysis of published clinical trials to elucidate the possible effect of vitamin D supplementation on the androgen levels in adult females with PCOS. PubMed, SCOPUS, and Google Scholar were searched to identify related articles published up to January 2017. Mean ± standard deviation (SD) of changes in serum total testosterone, sex hormone binding globulin (SHBG), and free testosterone were extracted to calculate Hedges’ g to be used as effect size for meta-analysis. DerSimonian and Liard random effects model was incorporated to summarize the effects. Six clinical trials with 183 participants aged 18–41 years with follow-up period between 3–24 weeks were included. Our analysis revealed that vitamin D supplementation significantly reduces total testosterone (Hedges’ g=−0.32, 95% CI: −0.55 to −0.10; p=0.005); this effect remained significant in single group trials after subgroup analysis. Vitamin D supplementation did not affect serum free testosterone (Hedges’ g=−0.21, 95% CI: −0.44 to 0.079; p=0.08) or SHBG levels (Hedges’ g=0, 95% CI, 0.22–0.22; p=0.98). The present systematic review and meta-analysis revealed that vitamin D supplementation might significantly affect serum total testosterone while it is not effective in improving other markers of androgenic profile. Future double-blind, placebo-controlled clinical trials are highly recommended.
Keywords: vitamin D; androgens; polycystic ovary syndrome; systematic review; meta-analysis